King David : literary aspects of characterization - Scher, Tal Michelle (Kaplan Centre for Jewish Studies, 2016)
This dissertation is based on the premise that the Bible, in addition to being a work of historical and theological significance, is also a work of literary significance. As such, the aim of the dissertation is to study the biblical figure of David as a literary character. In particular, it focuses on various techniques of characterization used to present this character to the reader. The primary texts examined in this dissertation are I Sam. 16 - I Kings 2:10, and Psalms 3, 7, 18, 34, 51, 52, 54, 56, 57, 59, 60, 63 and 142. In addition to these biblical texts, various biblical and literary critics are consulted, and their theories and arguments applied to this investigation of David as a literary character. In investigating David as a literary character, certain aspects of characterization theory are considered: direct and indirect techniques of characterization, and primary and secondary levels of characterization. Chapter One outlines these theoretical issues of characterization, which are discussed in greater detail in the chapters that follow. Chapter Two deals with the use of contrast as a characterization technique. Chapter Three examines character interaction. Chapter Four considers the function of motif in characterization. Chapter Five relates certain psalms and poems to the narrative texts, as they, too, perform a characterizing function. Chapter Six is a chapter of conclusion. It must be emphasized that the focus of this dissertation is primarily on the techniques and strategies used to present the character David, and less on the character himself. The emphasis is on the process, rather than on the product. The dissertation is in English. All biblical quotes are given in English translation, with English transliteration of Hebrew words when necessary. Bibliography: pages 187-194.